The Regenerative Effects of Hemostatic Plant Extract in Second Degree Burn Wound - Ozcan, Erhan Cahit; Senol, Sefa; Tokgoz, Yavuz; Kuloglu, Tuncay (Kemal Türker ULUTAŞ, 2017)
Introduction: The effects of Ankaferd Blood Stopper ABS , a hemostatic herbal agent, on wound healing of experimental second degree thermal burn model were analyzed in this study. Material and Methods: 24 wistar albino rats were used. All rat subjects were divided into 4 equal groups as control, burn control, Ankaferd Blood Stopper and serum physiologic. In all rats except for those in negative control group, second degree thermal burn was formed with metal plates heated on their backs. Biopsies were taken on 0th,7th,14th and 21st days. In tissue samples; they were evaluated in terms of fibroblast increase histopathologically, congestion, inflammatory cell increase and epithelization findings and they were also scored. The values obtained were compared statistically. Results: No significant difference was observed between groups with regard to fibroblast increase p>0.05 . On the 7th day, congestion values in burn control group was determined higher than ABS group p